Theoretical and methodological foundations for forming the social consciousness of future foreign language teachers in the age of information education (Journal of Educational Sciences, 2024)
The article deals with the topical issues of socially significant consciousness formation of future foreign language teachers. The authors analyzed the state and highlighted the prospects for the development of students’ socially significant consciousness in the conditions of open information space. As a result of studying this issue the necessity to correct the influence of various information from the Internet on students is emphasized. The article analyses the foreign and domestic scientific literature on the issue sought. Referring to the rapid development of the information paradigm of modern education, researchers have identified and systematized theoretical and methodological approaches to the formation of socially significant consciousness in the general information learning process. The outlined theoretical novelty of the study emphasizes its significance, which is expressed in the fact that the identified approaches will enrich the theory and increase the potential of pedagogical research in this direction. The practical significance of the study lies in the innovative technologies definition of modern general information learning with the use of media texts, to which the authors attributed CLIL- and analytical and situational technologies of work with authentic media texts from the Internet. Having defined the conceptual framework (substantive and procedural): purpose, content, organization, methods and forms, etc., the authors implemented them in the practice of training future foreign language teachers. Various methods of working with authentic media texts are widely presented in the article.Key words:  social consciousness, theoretical-methodological approaches, innovative technologies, CLIL-technologies, analytical-situational technologies.